SIKAP MASYARAKAT TERHADAP HUTAN DESA DI DUSUN MANJAU DESA LAMAN SATONG KECAMATAN MATAN HILIR UTARA KABUPATEN KETAPANG - Siregar, Fransiska Berliana; Surachman, Maman; wati, Pur (JURNAL HUTAN LESTARI, 2015)
Forests area that designated as village forest needs to be managed and maintained it’s sustainability. Since it is established as village forest,the people of Dusun Manjau attitudes about the village forest was unknown. By knowing the attitude of societiesabout the village forests, we’ll see the societies’s motivations and initiatives to maintain and preserve thesearea. This research aims to knowthe attitudes of the people about village forest in Dusun Manjau. The results of the research is that people who have a positive attitude about village forest in Dusun Manjau are people who respect’s the rules that relating to village forest, beside that they also know with continuing to maintain and preserve the village forest,and also to maintain the life and future of generation. In the other side, respondents who have negative attitude about the village forest is those that don’t care about the village forest and its existence. This attitude caused by several factors, among others, lack of awareness about the surrounding environment, lack of information about how importantto keep the village forest. According to the information from members of LPHD (Lembaga Pengelolaan Hutan Desa / Village Forest Management Council)in Dusun Manjau. There are education and socialization provided by NGO and stakeholders to the localpeople, but not all the people take participate in these activities. Keyword : Aittude, Dusun Manjau, village forest